Trust, Security, Comfort, and Social Presence Sebagai Prediktor Basic dan Advanced Virtual Agent Usage Intention - Candy Candy; Johny Budiman; Ahmad Esa Galang Malino; Darwin Darwin; Frendy Wijaya; Hendra Wijaya; Stewendy Stewendy (Universitas Multi Data Palembang, 2026)
Artificial intelligence (AI) has significantly improved efficiency in financial technology (fintech) services in Indonesia and globally. This study aims to analyze the perceptions of university students in Indonesia regarding the use of financial technology in an era of rapid AI development. In addition, the study examines students’ perspectives on fintech usage in relation to the security of users’ assets. The research employs a questionnaire-based method conducted across Indonesian universities, involving 217 university student respondents. The results indicate that psychological factors influence the intention to use virtual agents differently across basic and advanced digital financial services. Perceived security has a stronger effect on the adoption of virtual agents for routine transactions, whereas perceived convenience plays a key role in encouraging their use for more complex financial services. These findings highlight the importance of tailoring the design of AI-based virtual agents to the level of complexity of the financial services offered.